2001
DOI: 10.1103/physrevb.64.220502
|View full text |Cite
|
Sign up to set email alerts
|

Nondiverging vortex pinning barriers at low current densities across the putative elastic vortex-glass–vortex-liquid transition inYBa2Cu3

Abstract: A detailed analysis of the electric field-current density (EϪJ) characteristics of YBa 2 Cu 3 O 7Ϫ␦ films across the putative thermally induced elastic vortex-glass-vortex-liquid transition predicted by the E(J) curve scaling reveals that the expected increase of the collective pinning barriers with decreasing J is cut off in the low-J region, signaling a dissipation process which involves the plastic deformation of the vortex system. The temperature and magnetic field dependence of the pinning barriers at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…At long t, the averaged U * (DC) divided by T becomes of the order unity close to the IL (figure 1(b)), where one enters the thermally assisted flux flow (TAFF) regime [33], with a linear E( J) at low J, whereas the AC U * value from the main panel of figure 4 leads to a J exponent U * (AC)/T∼10.8. This suggests that the TAFF regime at long t just below the IL does not correspond with the thermally activated vortex hopping in the AC response, because the appearance of TAFF is only possible when U * /T3 [8,34], i.e., in the case of AC measurements, at significantly higher temperatures. Moreover, the logarithmic U AC (diverging at low J) would be in conflict with a TAFF regime, which, on the other hand, is entirely possible for the plastic vortex-creep (negative p) at long t (see figure 1(b)), with a finite pinning barrier in the low-J limit.…”
Section: Resultsmentioning
confidence: 99%
“…At long t, the averaged U * (DC) divided by T becomes of the order unity close to the IL (figure 1(b)), where one enters the thermally assisted flux flow (TAFF) regime [33], with a linear E( J) at low J, whereas the AC U * value from the main panel of figure 4 leads to a J exponent U * (AC)/T∼10.8. This suggests that the TAFF regime at long t just below the IL does not correspond with the thermally activated vortex hopping in the AC response, because the appearance of TAFF is only possible when U * /T3 [8,34], i.e., in the case of AC measurements, at significantly higher temperatures. Moreover, the logarithmic U AC (diverging at low J) would be in conflict with a TAFF regime, which, on the other hand, is entirely possible for the plastic vortex-creep (negative p) at long t (see figure 1(b)), with a finite pinning barrier in the low-J limit.…”
Section: Resultsmentioning
confidence: 99%
“…They further showed that this described data collected on a YBa 2 Cu 3 O 7−x crystals, in a regime in which there was other evidence of plastic dynamics, such as a decrease in U with magnetic field (whereas an increase is predicted for elastic creep). Consequently, it has become common to identify a change from elastic to plastic creep as a sudden change in slope on a log U − log(1/J) plot, identifying the plastic flow regime as U pl ∼ (1/J) p , for p < 0, and many studies have observed a sharp change in slope with (in some cases) strikingly linear behavior on both sides of the transition [23,25,29,48,[54][55][56][57][58][59][60][61][62][63]. At high temperatures and fields H > H ep in our samples, we see that the slope of the U * versus 1/J plot shown in Fig.…”
Section: B Plastic Deformations Of the Vortex Latticementioning
confidence: 99%